2013
DOI: 10.4049/jimmunol.1200653
|View full text |Cite
|
Sign up to set email alerts
|

Kidins220/ARMS Associates with B-Raf and the TCR, Promoting Sustained Erk Signaling in T Cells

Abstract: The activation kinetics of MAPK Erk are critical for T cell development and activation. In particular, sustained Erk signaling is required for T cell activation and effector functions, such as IL-2 production. Although Raf-1 triggers transient Erk activation, B-Raf is implicated in sustained Erk signaling after TCR stimulation. In this study, we show that B-Raf is dephosphorylated on its inhibitory serine 365 upon TCR triggering. However, it is unknown how B-Raf activation is coupled to the TCR. Using mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 73 publications
(93 reference statements)
10
43
0
Order By: Relevance
“…Many regulators of ERK signal intensity and duration have been identified (Andreadi et al, 2012), such as the linkage of B-Raf to prolonged ERK activation (Tsukamoto et al, 2004). B-Raf is thought to prolong ERK signaling through a newly described adaptor molecule, Kidins220, which is expressed in T lineage progenitors and associates with both the pre-TCR and γδTCR (Deswal et al, 2013). The duration of ERK signals has also been linked to the extent of heterodimerization of upstream signaling molecules, MEK1 and MEK2 (Catalanotti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many regulators of ERK signal intensity and duration have been identified (Andreadi et al, 2012), such as the linkage of B-Raf to prolonged ERK activation (Tsukamoto et al, 2004). B-Raf is thought to prolong ERK signaling through a newly described adaptor molecule, Kidins220, which is expressed in T lineage progenitors and associates with both the pre-TCR and γδTCR (Deswal et al, 2013). The duration of ERK signals has also been linked to the extent of heterodimerization of upstream signaling molecules, MEK1 and MEK2 (Catalanotti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to possible Rap1 interaction, novel binding partners of B-Raf in T cells have been found (46). Of interest, B-Raf was shown to interact with both Dock2 (dedicator of cytokinesis protein 2), a guanine nucleotide exchange factor known to specifically activate Rac, and IQGAP1 (Ras GTPase-activatinglike protein 1), a scaffolding protein known to interact with actin, Rac1, calmodulin, and Src (46 -48).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, ARMS has been shown to interact with all three Trk receptors (Trk A, Trk B, and Trk C), the p75 receptor, and the vascular endothelial growth factor (VEGF) receptor, and plays an important role in neurotrophin and VEGF signaling (Cesca et al , 2012; Kong et al , 2001). Further, a recent study demonstrated that ARMS can also interact with the T-cell receptor (TCR) to mediate the T-cell response via sustained activation of extracellular signal-regulated kinase (ERK) signaling (Deswal et al , 2013). In addition, a report using an ARMS knockout mouse model demonstrated that embryos lacking ARMS expression die at birth due to severe defects in neuronal and vascular development, including cardiac malformation (Cesca et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested ARMS to be a key regulator of neuronal survival and function mediated by neurotrophin receptors. Although ARMS is most strongly expressed in various neuronal cell types (Chen et al , 2012; Kong et al , 2001), its expression and function have recently been demonstrated in multiple peripheral immune cell types in mice (Li et al , 2013; Ni et al , 2011) as well as in human T-cells (Deswal et al , 2013; Jean-Mairet et al , 2011), and dendritic cells (Riol-Blanco et al , 2004). …”
Section: Introductionmentioning
confidence: 99%